Foreign Languages Training in Ukraine: Is teacher training having enough? - Olha Osova (Centre for Behaviour and Wellness Advocacy, 2017)
To ensure effective educational activity, it is necessary to take into account the common European and national tendencies of social development. These factors form the basis for modifications in educational pathways nowadays. This article presents the main modern priorities in the training system of trainee teachers. It has been proven that the use of foreign languages in the training system of trainee teachers helps them to accumulate considerable educational and potential development in the level of general and professional culture. It also affects their thinking culture, and subsequent communication with the globalized information-technological society. It provides them the skills to find their own place in the context of general and specific growth within the modern of many cultures.